2015
DOI: 10.1159/000441004
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-17A Levels Vary in Relapsing-Remitting Multiple Sclerosis Patients in Association with Their Age, Treatment and the Time of Evolution of the Disease

Abstract: Objective: The present study was specifically designed to discern the possible existence of subgroups of patients with the relapsing-remitting form of multiple sclerosis (RRMS) depending on their gender, age, disease stage (relapsing or remitting), time of disease evolution and response to different treatments. Methods: We analyzed samples from patients with RRMS (50 females and 32 males) and healthy individuals (25 matched for age and gender) and determined serum concentrations of IFN-γ, IL-10 and IL-17A. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 40 publications
4
4
0
Order By: Relevance
“…No correlation was observed between EDSS scores and IL-17A expression in female patients, as also observed by other studies [23,24]. In fact, many chronic inflammatory disorders such as rheumatoid arthritis, psoriasis, and MS are associated with high IL-17A levels but, according to the current best knowledge, variations in IL-17 were not previously reported, which could be important for the various phases of the disease and its heterogeneity [26]. Another study that detected the relationship between IL-17 and insulin resistance found a crucial role of IL-17 in autoimmune disease [27].…”
Section: Interleukin-17asupporting
confidence: 65%
See 1 more Smart Citation
“…No correlation was observed between EDSS scores and IL-17A expression in female patients, as also observed by other studies [23,24]. In fact, many chronic inflammatory disorders such as rheumatoid arthritis, psoriasis, and MS are associated with high IL-17A levels but, according to the current best knowledge, variations in IL-17 were not previously reported, which could be important for the various phases of the disease and its heterogeneity [26]. Another study that detected the relationship between IL-17 and insulin resistance found a crucial role of IL-17 in autoimmune disease [27].…”
Section: Interleukin-17asupporting
confidence: 65%
“…Along with the alteration in cytokine production in the periphery, these data demonstrate persistent pro-inflammatory activation even during the clinically stable period of the disease, although most patients enrolled in this study are in the RRMS stage [24]. Furthermore, previous research detected lower levels of IL-17A in female MS patients [25], while other reports showed an opposite increase in the levels of this cytokine [26].…”
Section: Interleukin-17asupporting
confidence: 53%
“…There was a statistically significant difference between the MS-patients and the HC regarding sex and age. It has been shown previously that these parameters might affect the levels of at least some cytokines in healthy individuals [ 20 ] as well as in RRMS [ 21 ] but not for any of the cytokines included in our final results. The difference in mean age was in a range that any major impact on the conclusions is unlikely.…”
Section: Discussionmentioning
confidence: 77%
“…However, it is difficult to establish a correlation between CNS-infiltrating and peripheral T cell subsets. In this respect, it is necessary to consider the possible existence of subgroups of patients, depending on treatment and time of disease evolution [ 127 ] to identify the correlations of these subgroups with variations in the T cell subsets present in MS pathogenesis.…”
Section: Cells Involved In Msmentioning
confidence: 99%
“…However, it is difficult to correlate these levels with the evolution of the disease. Thus, the existence could be considered of subgroups of patients with specific characteristics, considering age, treatment, and time to disease progression [ 127 ]. In this respect, it would be possible for T cell subsets to also vary according to these subgroups in patients with MS.…”
Section: Cells Involved In Msmentioning
confidence: 99%